Navigating the dementia caregiving journey: A scoping review protocol of interventions and their responsiveness to caregivers’ evolving needs across the illness trajectory - Kokorelias, Kristina M.; Stall, Nathan M.; Wasilewski, Marina; Gignac, Monique A.M.; Rittenberg, Nira; Singh, Hardeep; Dove, Erica; Harris, Maurita; Beleno, Ron; Naglie, Gary; Cameron, Jill I. (PloS one, 2025)
Family caregivers of persons with dementia (PWD) provide critical and often sustained support across the dementia trajectory. Despite growing recognition of their evolving needs, many interventions remain episodic and not tailored to different caregiving phases. Frameworks like the Timing It Right (TIR) and the Caregiver-Identified Phases of Alzheimer's Disease (CIP-AD) offer structured approaches to understanding how caregiver needs change over time. However, little is known about whether current interventions align with these phase-specific needs. This scoping review aims to (1) explore the extent to which existing dementia caregiving interventions address different stages of the caregiving journey or dementia progression; (2) summarize and characterize these interventions using the Template for Intervention Description and Replication (TIDieR) checklist; and (3) identify characteristics of the populations targeted by these interventions. Following JBI methodology and the PRISMA-ScR checklist, we will conduct a scoping review of randomized controlled trials, non-randomized controlled trials, and quasi-experimental studies focused on interventions for unpaid family caregivers of community-dwelling PWD. Studies will be included if they address at least one phase of the dementia trajectory and are delivered in community-based settings. A comprehensive search of six databases from 1995 to 2025 will be developed and peer-reviewed using the PRESS framework. Data will be extracted using a standardized form and analyzed thematically. This review will map how dementia caregiving interventions address the evolving needs of caregivers over time and inform future development and implementation of phase-responsive support strategies. The findings will guide research, policy, and practice in creating caregiver-centered interventions that reflect the realities of caregiving across the dementia continuum.